PHYSICAL-CHEMICAL AND SENSORY EVALUATION OF CUPUAÇU NECTAR (REMUNOM, 2025)
Cupuaçu is a typical fruit from the Amazon, where it has its origin, being widely consumed and appreciated by the local population, and even nationally and internationally, being widely used in various food formulations and in a variety of drinks, such as chocolates, sweets, juices and liqueurs. The present work prepared a cupuaçu pulp nectar from a municipality in Pará, investigated the physicochemical properties of this nectar and carried out a sensory analysis of it using one hundred untrained tasters. The results obtained suggest that the physicochemical properties were in accordance with findings in the literature and the sensory analysis demonstrated good acceptance of the product. Therefore, cupuaçu nectar can be a suitable product for consumption of the fruit, especially during the period between fruit harvests.